A STUDY OF WASTES GENERATED IN THE PRODUCTION OF LEAD - S. L. Rovin; S. V. Grigoriev (Литьë и металлургия)
Lead-containing wastes amount to more than half of the waste of non-ferrous metals formed in Belarus. At the same these wastes are the least studied and the most toxic of the metal wastes. The bulk of them consists of lead-acid batteries, 50–60% of the mass of which is oxide-sulphate lead paste. The article presents the results of a study of the composition and properties of characteristic lead-containing wastes generated both in the operation of lead-containing products and in the production of lead (slag, dust aspiration, etc.). Obtained data allow to optimize the technological regimes of processing of wastes: consumption of fluxes and temperature – time regime of the lead melting.